Pengaruh ROA, CR, dan DER terhadap harga saham perusahaan manufaktur subsektor food and beverage yang terdaftar di BEI Tahun 2015-2019 - Azari Lubis , Zulham; Firdaus Hutahaean , Thomas; Kesuma , Silvia; Veronika Karin , Anju (Jurnal Paradigma Ekonomika, 2021)
This study was made to know the effect of return on assets, current ratio, and debt to equity ratio on stock prices of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange in the 2015-2019 period. This study uses a quantitative approach with a descriptive statistical analysis type. The data used is sourced from financial data on the Indonesia Stock Exchange and has been selected based on predetermined criteria. The population in this study amounted to 31 companies, using a purposive sample. The samples obtained were ten companies in the last five years. The results of this study indicate that partially the current ratio and debt to equity ratio do not have a positive and significant effect on stock prices. Partly, the return on assets has a positive and significant impact on stock prices. Return on assets, current ratio, and debt to equity ratio as independent variables simultaneously have a substantial effect on the variable stock price of manufacturing companies. Â